Reflective Teacher Pilot Testing of Activity Based Module for Teaching Social Sciences - Singh, Jaya (JOURNAL OF INDIAN EDUCATION, 2014)
The paper advocates activity based pedagogy for reflective teachers who can reflect upon their practices to ensure equity in participation and concentrate on execution of social justice while transacting the curriculum. The other purpose circumvents around needs for changes found in the mode of teaching which advocates status quo and perpetuates personal prejudices in the classroom. Training for reflective teachers is needed to develop competencies for successfully carrying out reform in the area of curricula so that teachers engage all the students and integrate diversity in the classroom. It is advisable for teachers to engage in an intellectual discourse with their peers to exchange their insight and reflect upon their teaching. It was on this challenge that two modules of activity based pedagogy in economics were tested. The paper attempts to reflect upon pilot testing of two modules which were practised during the training session meant for trained graduate teachers (TGT) in social sciences. The feedback and experiences suggest that the execution of the two modules where the participants engage in discussion, debate and enact critical issues are more successful than the lecture method where the participants sit as passive learners.